The CGIAR Food Systems Accelerator: cohort one. Gender Equality and Social Inclusion technical assistance report - Njiru, A.; Bohjanen, C.; Sewe, L.; Nortje, Karen; Enokenwa Baa, Ojongetakah (International Water Management Institute (IWMI), 2023)
The CGIAR Food Systems Accelerator (CFSA) was launched as part of the activities under the CGIAR Initiative on Diversification in East and South Africa (Ukama Ustawi), with the main objectives, of strengthening food systems by scaling climate-smart food system innovations (through strategic support of commercially viable and inclusive climate-smart agribusinesses), develop a pipeline of inclusive climate-smart agribusinesses in East and Southern Africa, support inclusive climate-smart agribusinesses (through a 6-month program that provides investment readiness and business development, climate-smart agriculture (CSA) and impact measurement and management (IMM) technical assistance, GESI strengthening, coaching and mentoring) and facilitate access to finance through de-risking grants to scale CSA innovations and business models. In the inaugural CFSA cohort, 10 agribusinesses (Accelerator Partners) were supported from Kenya (4), Rwanda (2) Uganda (2), and Zambia (2).